Efecto de la fertilización nitrogenada e intervalos de corte sobre el valor nutritivo potencial del pasto King grass (Pennisetum purpureum x Pennisetum typhoides). Durante la época lluviosa (ING) - Fallas, Edgar (1987)
Data from a experiment that utilized King Grass forage (Pennisetum purpureum x Pennisetum typhoides) with four nitrogen fertilization levels (0, 100, 200 and 300 kg Ha-1) and five harvest intervals (35, 49, 63, 77 and 91 d) were analyzed by an analysis of variance under an split plot design. The study variables were dry matter production (DM kg Ha-1 harvest-1), crude protein production (CP kg Ha-1 harvest-1) and its CP% contents and in vitro dry matter digestibility (I.V.D.M.D). The research was done in National University, Santa Lucía Research Farms at Heredia, Costa Rica. The climatic characteristics during the research period were 19.7°C temperature and 2.000 mm rainfall mean. Dry matter production was increased by the nitrogen fertilization (P=<0.05) CP production also was incremented by fertilization. However the I.V.D.M.D. was not affected by the fertilizer treatments.The harvest period did increase the DM production (P=<0.05) and the CP production by cutting but there were a reduction in the CP % (P=<0.05) and I.V.D.M.D. % were fond no significative (statically) interaction among nitrogen levels and harvest period.A preliminary recommendations for this cutting grass under our conditions are a harvest period of 63-77 d with a nitrogenous fertilization between 100 to 200 kg Ha-1.